The Written Source as a Corroborative Element of Sound Changes: Onomastic Evidence - Cerrón-Palomino, Rodolfo (2022)
Scientific etymology, as opposed to the naive or the purely impressionistic, finds its strongest support in historical linguistics, and, in turn, within this discipline, in its consecratory discovery of the regularity of sound change. By virtue of this attribute, the researcher, in this case the etymologist, is capable of finding the etymology of a given term of which he wasn’t yet sure. Furthermore, by taking into account the regularity of the change, he can predict it, even in absence of available corroborating corpus at hand. Empirical confirmation for an etymological prospect can be found either with the discovery of novel dialect forms not previously known, or by virtue of unsuspected evidence provided by philologically interpreted written record. The present work aims to demonstrate the importance of written source, printed or manuscript, as a rich and inexhaustible vein of information thanks to which the hypothetical postulations made by the etymologist can be tested and eventually corroborated. More specifically, this essay will test the impressive predictive potential of regular sound change by using examples taken from Quechua and Aymara. Our exposition goes as follows: after a general introduction on the development of historical linguistics in the Andean region, we focus our discussion on regular sound change and its predictive nature within Andean linguistics studies with corroborating evidence of dialectal as well as documental (published) material. A fourth section provides new and revealing archival evidence. In sum, the evidence provided, both printed or unpublished, revolves around the etymology of onomastic terms such as <Inca>, a nobility title, and <Yauyos>, a well-known Andean ethno-toponym.